Neuronal mechanisms of learning and memory revealed by spatial and temporal suppression of neurotransmission using shibirets1, a temperature-sensitive dynamin mutant gene in Drosophila melanogaster - Kasuya, Junko; Ishimoto, Hiroshi; Kitamoto, Toshihiro (Frontiers in Molecular Neuroscience, 2009)
The fruit fly Drosophila melanogaster is an excellent model organism to identify genes and genetic pathways important for learning and memory. However, its small size makes surgical treatment and electrophysiological manipulation technically difficult, hampering the functional analysis of neuronal circuits that play critical roles in memory processing. To circumvent this problem, we developed a unique experimental strategy that uses the temperature-sensitive allele of the Drosophila dynamin gene, shibirets1 (shits1), in combination with the GAL4/UAS expression system. This strategy allows for rapid and reversible perturbation of synaptic neurotransmission in identifiable neurons, and analysis of the behavioral consequences of such manipulation in free-moving animals. Since its introduction in 2001, this GAL4/UAS-shits1 strategy has been widely used to study the neuronal basis of learning and memory. This review focuses on how this strategy has revitalized Drosophila memory research, and contributed to our understanding of dynamic neuronal processes that control various aspects of memory.